ASUHAN KEBIDANAN KOMPREHENSIF DENGAN KOMPLEMENTER PADA NY. “L” DI BIDAN PRAKTIK MANDIRI NY. “Y” DESA SUMBERMULYO KECAMATAN JOGOROTO KABUPATEN JOMBANG - Nadhira Ariviona; Ardiyanti Hidayah; Siti Nur Farida (Library Unit of the College of Health Science Husada Jombang, 2023)
Introduction: In a person's life cycle, pregnancy, childbirth, postpartum, newborn, and pregnancy are physiological events, but there are several hazards or conditions that can endanger the mother and newborn, and can even cause death. One indicator of the development of health status is maternal and infant mortality, which is used to evaluate the success of health services and other health development programs. Objectives: The aim of midwifery care is to reduce the incidence of maternal and infant mortality. Methods: Midwifery care in the third trimester of pregnancy for Mrs.